Richard III : Fact, Myth, Fiction - Rajala, Anna Ilona; Uotinen, Timo (Cambridge University Press, 2022)
In this chapter we study representations of the last Plantagenet king of England, Richard III, relating his myth and history to the discovery of his body in 2012 in a Leicester car park. Focusing on the body of Richard, we address the unique cross-genre nexus between historiography, Shakespeare’s drama, and modern medical writing, to evaluate the mythical, factual, fictitious, and scientific depictions of Richard. Our aim is to find out what role interpretation and truth play in the differing genres and what kind of implications interpretation and truth have for these genres regarding the body of Richard. We draw on literary studies, disability studies, health sciences, and especially the work of Horkheimer and Adorno to argue that, in the case of Richard, myth and science are modes of representation that seek to control truth and rely on interpretation and speculation to draw conclusions about uncertain and unknowable things. The post-excavation science does not oppose myth and fiction, but perpetuates the mythology surrounding Richard, whereas Shakespeare drama has ‘truth content’ in challenging conceptions of disability. Moreover, this cross-genre nexus demonstrates the inseparability of subjectivity from interpretation and that truth never appears unmediated. Thus, making subjectivity visible in analyses is indispensible for a higher fidelity to truth.
Keywords: historia; myytit; kirjallisuudentutkimus; historiankirjoitus; tulkinta